GREEN STRATEGY MODERATE THE EFFECT OF CARBON EMISSION DISCLOSURE AND ENVIRONMENTAL PERFORMANCE ON FIRM VALUE - Sistya Rachmawati (International Journal of Contemporary Accounting, 2021)
The purpose of this study is to examine and analyze: (1) The effect of disclosure of carbon emissions and environmental performance on firm value. (2) Effect of green strategy on firm value (3) Green strategy Moderates the effect of disclosure of carbon emissions and environmental performance on firm value. Quantitative research uses secondary data taken by purposive sampling from annual reports and sustainable reports of manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The data is processed by panel regression. The conclusion of this study (1) Disclosure of carbon emissions has no effect on firm value. (2) Environmental performance and green strategy have a significant positive effect on firm value. (3) The green strategy strengthens the effect of carbon emission disclosure on firm value. (4) The green strategy is not proven to strengthen environmental performance on company value. So, the green strategy only acts as a predictor or independent variable.